Smarter faster just-in-time hemorrhage control: A pilot evaluation of remotely piloted aircraft system delivered STOP-THE-BLEED equipment with just-in-time remote telementored deployment. Issue 1 (January 2023) - Kirkpatrick, Andrew W.; McKee, Jessica L.; Conly, John M.; Flemons, Kristin; Hawkins, Wade
Abstract: Introduction: Remotely Piloted Aircraft Systems (RPAS) can access patients inaccessible to traditional rescue. Just-in-time remote telementoring (RTM) of naïve users to self-care could potentially address challenges in salvaging exsanguination in remote environments. Methods: An exsanguination self-application task was established in a wilderness location. Three volunteers-initiated distress calls to prompt RPAS precision delivered STOP-THE-BLEED kits, after which a remote mentor directed the volunteers how to self-care. Results: Limited connectivity prevented video, however each volunteer delivered images and initiated conversation with the mentor pre-RPAS arrival. Thereafter, all subjects were able to unpack and deploy hemorrhage control adjuncts under verbal direction, and to simulate self-application. All subjects were able to successfully apply wound-clamps, tourniquets, and pack wounds although one had insufficient pressure. Discussion: RPASs can deliver supplies long before human rescuers, and communication connectivity might allow remote mentoring in device application. Further development of technology and self-care paradigms for exsanguination are encouraged. Highlights: Bleeding to death is the most preventable cause of post-injury bleeding. The earliest possible hemorrhage control is required to save lives, especially with self-care. Potentially self-applied hemorrhage control adjuncts can be delivered by RPAS before traditional human responses. Conscious victims may be able to utilize unfamiliar hemorrhage control adjuncts with remote telementored direction. Further research is urgently required into the remotely piloted aircraft systems delivery of hemorrhage control adjuncts.